Biosolid and sugarcane filter cake in the composition of organomineral fertilizer on soybean responses - da Mota, Raquel Pinheiro; de Camargo, Reginaldo; Lemes, Ernane Miranda; Lana, Regina Maria Quintão; de Almeida, Risely Ferraz [UNESP]; de Moraes, Emmerson Rodrigues (Springer Nature, 2019)
Purpose: Organomineral fertilizers formulated from different organic sources have been studied for the fertilization of several crops. Filter cake is currently one of the most used sources of organic matter; however, sewage sludge also presents characteristics of agronomic interest, being one of the major environmental problems in Brazil. In this sense, the efficiency of pelletized organomineral fertilizers produced with both sources were evaluated for the development of soybean under different fertilization levels. Methods: The experiment was carried out in greenhouse conditions. The soil was characterized as Red Eutrophic Oxisol. The experimental design was randomized block design in a 2 × 4 + 2 factorial scheme, corresponding to two sources of organic matter (sugarcane filter cake and treated sewage sludge), in four doses (50, 75, 100 and 125% of recommendation for soybean cultivation), as well as a mineral fertilization and no-fertilization treatments. The plant development was evaluated (stem diameter, plant height and chlorophylls a and b) at 30, 60 and 90 days after sowing. Results: Organomineral fertilizers formulated from sanitized sewage sludge or sugarcane filter cake promote a higher soybean plant height in relation to mineral fertilizer, especially after the middle of the crop cycle. The level of fertilization referring to 75% of the recommended dose for soybean, when made with sanitized sewage sludge or filter cake, resulted in large stem diameter in relation to mineral fertilization. Conclusion: Organomineral fertilizers based on sanitized sewage sludge or filter cake promote increases in soybean characteristics up to 90 days.
Keywords: Chlorophylls; Glycine max; Sewage sludge; Sugarcane mill filter cake